Retaining Middle Managers in China - Li, Bo (2008)
Extensive media reports and recent studies have aroused the retention of talented managers as the biggest management challenge for foreign firms in China. Bearing the highest turnover rate, middle managers are considered to be the most demanding group on the labor market. The purpose of this thesis is to get a better understanding of the measures foreign companies in China are taking to retain employees and the impact of them in the retention of middle managers. Case studies are conducted on six companies from the Elevator Industry in China. Focusing on three areas of Compensation, Organizational Culture and Employee Development, empirical data is collected through qualitative interviews with both Human Resource managers and Chinese middle managers. Combining the outcomes from theoretical study with results from empirical investigation, Employee Development emerges as the most important factor in retaining middle managers. Further, the importance of leader's role is also stressed due to its wide influence on all the functions in the organization. After a discussion on the limitation of the thesis, the thesis ends with recommendations for future researches on areas of interests.